Analysis of Factors Causing the Decline of the Oversight System of the Consultative Body of Malenge Village, Tojo Una-Una Regency - Wahyu Hidayat N. Ahmadong (Universitas Negeri Gorontalo, 2023)
The purpose of this research is to find out the causal factors that influence the effectiveness of the supervision system for the Malenge village government, Tojo Una-una Regency. The research method used is an empirical research method using a qualitative approach. The results of this study are that the productivity of BPD performance in Malenge Village is still less efficient in carrying out its daily tasks and functions. This can be seen from the many (input) aspirations of the people who entered the BPD, only one was produced. Against the relatively large differences between the actual use carried out. Some of the examples are the regulations implemented by the BPD, only the Perdes regarding the Village Revenue and Expenditure Budget. From the results of the discussion above, we can conclude that the productivity of the BPD in Malenge Village is not good. Because it is not able to produce products of legislation for the Village in accordance with what is expected by the community.